Early Cretaceous bivalves of the Neuquén Basin, west-central Argentina: Notes on taxonomy, palaeobiogeography and palaeoecology - Lazo, Dario Gustavo (2007)
This paper provides an updated taxonomic inventory of the bivalve fauna collected in the Pilmatué Member of the Agrio Formation of the Neuquén Basin, west-central Argentina, places the fauna in its palaeobiogeographic setting, and addresses its palaeoecological significance. Thirty-one Late Valanginian to Early Hauterivian bivalve species within 24 genera were identified. A large part (32%) of the identified bivalve species occur over a wide geographical area: from the Pacific coast of South America to Europe, North Africa, Central Asia and East and South Africa; some are also recorded in Japan. A relatively high degree of endemism (26%) is shown, suggesting that some of the bivalve species had barriers to their dispersal; larval strategy and length of larval development were probably important. A significant number (42%) of the bivalve taxa are left in open nomenclature as they are probably new species. Bivalve guilds are described to interpret palaeoecology, in particular the ecospace utilization. Guilds are based on tiering, life habit, and feeding category. Eight guilds are recognized: free-lying epifaunal, cemented epifaunal, epibyssate, boring, endobyssate, shallow burrowing, deep burrowing and deep burrowing with symbiotic bacteria. The fauna is composed only of suspension-feeders indicating that food resources were dominantly in suspension, in agreement with the predominantly shallow-water aspect of the study deposits. The ecospace utilization in the shoreface is broader than in the offshore shelf, suggesting more favourable living conditions and/or a wider range of different habitat types represented.